Lucky investors trade more : evidence from a large and salient exogenous price shock - Brito, Matheus Carrijo (2022)
This paper examines the impact of luck on retail investors’ trading activity. We document an increase in trading activity and a worsening in the performance of lucky investors. We considered lucky investors who sold stock before an unexpected environmental disaster that caused a significant devaluation of this stock. After the event, lucky investors present 11% of portfolio turnover, 46% of numbers of trade, and 35% of the number of days with trade higher than similar investors. Also, the portfolio return risk-unadjusted is 6% and adjusted is 4% lower for lucky investors. Placebo tests indicate that our results are due to this specific stock by investors that sold this stock, and no effect is found using past outcomes.